Ice is nice! all about the north and south poles - Worth, Bonnie; Mathieu, Joe; Ruiz, Aristides (London A Random House Group Cpmpany, 2011)
The Cat in the Hat takes Sally and Dick to visit the North and South Poles, where they mingle with native animals-reindeer, musk oxen, polar bears, caribou, and all sorts of penguins. They discover how the animals stay warm in the freezing cold, learn why it's colder at the South Pole than at the North Pole, find out that one pole is located on land and the other isn't, and learn that scientists are studying climate change to keep both poles icy cold
"I'm Ready for reading"
English stories
2
Keywords: English stories